Creatine Prevents the Structural and Functional Damage to Mitochondria in Myogenic, Oxidatively Stressed C2C12 Cells and Restores Their Differentiation Capacity. (17th August 2016) - Barbieri, Elena; Guescini, Michele; Calcabrini, Cinzia; Vallorani, Luciana; Diaz, Anna Rita; Fimognari, Carmela; Canonico, Barbara; Luchetti, Francesca; Papa, Stefano; Battistelli, Michela; Falcieri, Elisabetta; Romanello, Vanina; et al.
Abstract : Creatine (Cr) is a nutritional supplement promoting a number of health benefits. Indeed Cr has been shown to be beneficial in disease-induced muscle atrophy, improve rehabilitation, and afford mild antioxidant activity. The beneficial effects are likely to derive from pleiotropic interactions. In accord with this notion, we previously demonstrated that multiple pleiotropic effects, including preservation of mitochondrial damage, account for the capacity of Cr to prevent the differentiation arrest caused by oxidative stress in C2C12 myoblasts. Given the importance of mitochondria in supporting the myogenic process, here we further explored the protective effects of Cr on the structure, function, and networking of these organelles in C2C12 cells differentiating under oxidative stressing conditions; the effects on the energy sensor AMPK, on PGC-1 α, which is involved in mitochondrial biogenesis and its downstream effector Tfam were also investigated. Our results indicate that damage to mitochondria is crucial in the differentiation imbalance caused by oxidative stress and that the Cr-prevention of these injuries is invariably associated with the recovery of the normal myogenic capacity. We also found that Cr activates AMPK and induces an upregulation of PGC-1 α expression, two events which are likely to contribute to the protection of mitochondrial quality and function.